THE INFLUENCE OF SOWING RATE ON THE CONTINUATION OF THE GROWTH PERIOD OF OILY FLAX VARIETIES - Ismatullaeva Azizakhon Askarjon kizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: Oil flax varieties showed the ability to germinate at the same time according to the planting criteria. A difference was observed between the varieties in the days of transition from the budding phase to the phases, and the ripening of the crop was determined in 102-105 days. It was observed that ripening was delayed by 1-2 days in comparison to the options where the sowing rate was 4.0 million pieces/ha, compared to 5.0 and 6.0 million pieces/ha. It was found that Fliz and Biryuza varieties ripened 2-5 days earlier than the control variety Bahorikor.